Edukasi Peningkatan Partisipasi Masyarakat Dalam Pengembangan Desa Wisata Pasca Pandemi Covid-19 di Desa Cikolelet Kabupaten Serang - Rahmawati, Rahmawati; Ilhan S, Afiatta; Imron, Imron (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Sultan Ageng Tirtayasa, 2024)
Community participation in the development of tourism villages is the main thing. The community-based tourism approach strongly emphasizes the active involvement of the tourism village community. However, since the Covid-19 pandemic there has been a decline in the number of tourists and the impact on the decline in